Viral Infections of the Central Nervous System in Qatar: Epidemiology, Pathogenesis and Clinical Outcomes. (4th October 2017) - Abid, Fatma Ben; Abukhattab, Mohammed; Salameh, Obada; Gohar, Ahmed; Al Masalmani, Muna; Al-Khal, Abdullatif; Butt, Adeel
Abstract: Background: Viral central nervous system (CNS) infections are common causes of morbidity and mortality globally. There are no existing data about viral CNS infections in Gulf Cooperation Council countries. We conducted this study to determine the etiology, clinical and epidimiological characteristics, and outcomes of viral central nerveous system infection in patients in Qatar. Methods: We retrospectively evaluated all cerebrospinal fluid findings from January 2011–March 2015 at any of the 7 hospitals in the Hamad Medical Corporation. We included those with an abnormal CSF findings and excluded those with missing medical records, no clinical evidence of CNS infection and those with proven bacterial infection. Based on pre-defined clinical and CSF (lab, culture, PCR) criteria, patients were classified as having meningitis, meningoencephalitis, encephalitis or myelitis. We reviewed the laboratory results to determine the proportion of persons with confirmed viral etiology. Results: Among 7690 patients with available CSF results, 550 cases met the case definition criteria for viral CNS infection (meningitis 75%; meningoencephalitis 16%; encephalitis 9%; myelitis 0.4%). Two-thirds (65%) were male and 50% were between 16-60 years old. The most common presenting signs and symptoms are listed in the table. Persons of Southeast Asian origin accounted for 39.6% of all infections. A definitive virologic etiologic agent was found in 38%, with enterovirus being the most common (44.3%) followed by Epstein–Barr virus (31%) and varicella-zoster virus (12.4%). The clinical outcome was overall good, only 2 cases died and the rest were discharged to home. Among those with confirmed viral etiology, 83.8% received ceftriaxone (mean duration 7.3 ± 5.2 days), 38% received vancomycin (mean duration 2.7 ± 5.4 days) and 38% received at least one other antibiotic. Conclusion: Viral etiology is common among those evaluated for CNS infection in Qatar, and is most commonly seen in Southeast Asian immigrants. Clinical outcomes are generally excellent in this group of patients. Antibiotics are overly used even when a viral etiology is confirmed. There is a need for clinician education regarding etiology and treatment of CNS infections. Disclosures: A. Butt, Merck: Investigator, Grant recipient